EFEKTIVITAS BADAN USAHA MILIK NAGARI DALAM MENINGKATKAN PENDAPATAN ASLI NAGARI DI NAGARI KATAPING KABUPATEN PADANG PARIAMAN - Anisa Safitri; Jumiati Jumiati (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
The purpose of this research is to describe and understand first, how the effectiveness of Nagari Owned Enterprises in increasing Nagari Original Income in Nagari Kataping second, what are the obstacles encountered in making Nagari Owned Enterprises effective in increasing Nagari Original Income in Nagari Kataping third, what efforts are being made to make Nagari-Owned Enterprises effective in increasing Asli Nagari's income in Nagari Kataping. This research uses qualitative methods and descriptive approaches. The research was conducted at Nagari Kataping location, Batang Anai District, Padang Pariaman Regency. Research informants are determined by technique purposive sampling. The data used in this research are secondary data and primary data. Data collection was carried out by means of observation, interviews, and documentation. So that the data obtained can be concluded from the data obtained in the field. The conclusion of this study is the effectiveness of Nagari-owned enterprises (BUMNag) in increasing Nagari Original Income in Nagari Kataping can not be effective. This is because in the management of the Nagari-Owned Enterprises (BUMNag) business unit that is less competent, the results of the business being managed have no development and are estimated to be losing money.